1996
DOI: 10.1006/viro.1996.0032
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cells Display Separate Receptors for Papillomavirus VLPs and for Soluble L1 Capsid Protein

Abstract: We examined the distribution of putative receptors for papillomavirus (PV) capsid proteins on various cell types, using either Hexahis HPV6b L1 fusion protein or synthetic HPV6b virus-like particles (VLPs). Specific, saturable binding of VLPs to CV-1 cells was demonstrated using 35S-labeled VLPs, with an average receptor number of 1 x 10(4)/cell and a binding affinity constant (Ka) of 4 x 10(7) M. VLP binding was quantitated by flow cytometry using a monoclonal antibody to the L1 capsid protein. Intense staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…This concept is further supported by the successful application of virus-like particles of other viruses for the characterization of virus-host interactions. Virus-like particle-based binding and entry systems have been developed for papillomavirus (17,24,28,37,42,53), rotavirus (22,23), and Norwalk virus (45,50).…”
Section: Discussionmentioning
confidence: 99%
“…This concept is further supported by the successful application of virus-like particles of other viruses for the characterization of virus-host interactions. Virus-like particle-based binding and entry systems have been developed for papillomavirus (17,24,28,37,42,53), rotavirus (22,23), and Norwalk virus (45,50).…”
Section: Discussionmentioning
confidence: 99%
“…VLPs with a density of 1.28 g/ml were collected and dialyzed extensively against PBS (13). Construction of baculovirus encoding HPV6bL1, HPV11L1, HPV16L1, bovine PV1L1 (BPV1L1), BPV1L1/HIVIIIbp18I10CTL (p18VLPs), and BPV1L1/HPV16E7CTL (E7VLPs) recombinant protein has been described elsewhere (13,26,27). Samples were subjected to analysis by transmission electron microscopy and immunoblotting to confirm the identity and integrity of the VLPs.…”
Section: Production Of Rvlpsmentioning
confidence: 99%
“…According to previous estimates (25,36), only 20,000 VLPs can bind to a given cell at saturation, whereas proteoglycans are common on all cells, with up to 10 6 molecules per cell (37). It is therefore tempting to speculate that a specific proteoglycan may mediate virion attachment.…”
mentioning
confidence: 99%
“…Virus-like particles (VLPs) generated by synthesis of the capsid proteins L1 and L2 in various expression systems (18,27,35) have shed some light on the mode of interaction between the cell surface and the viral capsid (26,24,36). It was demonstrated that the binding moiety on cell surfaces is highly conserved within the animal kingdom and that, with few exceptions, all cell lines tested were able to bind VLPs (25,36). In addition, VLPs generated from the capsid proteins of different papillomaviruses were shown to compete for the same binding receptor (26).…”
mentioning
confidence: 99%